Discussion of production techniques for speech-aids - KAMIYA, Mitsuo; NATSUME, Nagato; SAITO, Naoki; YOSHIDA, Katsuhiro; MASUDA, Hiroo; IKEMORI, Yoshiyuki (Japanese Journal of Oral and Maxillofacial Surgery, 1994)
Production of the wire structure for speech-aids demands a high degree of skill. In this study, we determined the wire structure for speech-aids, using lead foil and cephalometric radiograms. In the region of the soft palate, the wire structure was decided using lead foil, and in the region of the velopharyngeal space, the structure was decided using cephalometric radiograms. Such techniques can be mastered readily by relatively inexperienced individuals.